JUAL BELI BAJU GAMIS DENGAN SISTEM KONSINYASI DALAM PERSPEKTIF HUKUM ISLAM: Studi Kasus di Nurvi Collection, Soreang, Kab. Bandung, Jawa Barat - Raden Dias Syaefulloh; Ahmad Asrof Fitri (Melati Institute, 2022)
Trading as an effort to meet human needs in financing their lives is a recommendation to be carried out by Muslims. In today's life, humans cannot be separated from a transaction, namely buying and selling. Buying and selling is a transaction carried out by the exchange of goods and money. Along with the passage of time, economic activity is growing, one of which is the consignment system. The practice of buying and selling at the Nurvi Collection is carried out on consignment where the goods sold are directly deposited with the owner and the seller receives a commission. The objectives of this study are: To find out the consignment system in the practice of buying and selling robes at the Nurvi Collection and to find out the consignment system in the perspective of Islamic law on the practice of buying and selling robes at the Nurvi Collection. Types of research conducted by researchers are: field research (field research). The researcher uses a qualitative approach and the data collection uses observation, interviews, and documentation techniques. Then the data were analyzed using the inductive method, namely a discussion that begins with observations first, then draws conclusions based on these observations. Research Results: first, The practice of buying and selling robes that occurs at the Nurvi Collection is by using a consignment system, namely buying and selling of robes between the owner and the agent. When a transaction occurs, namely in terms of buying and selling robes with a consignment system, there is a prior agreement between the owner and the agent. The payment system is according to the goods sold that are not sold will return to the owner. Second, The practice of buying and selling robes with a consignment system according to Islamic law is allowed because basically the consignment system is the practice of depositing sales goods with a commission or ujrah, so the practice of consignment includes an ijarah contract or wakalah bil ujrah contract.